Antiglycolipid autoantibody detected in the sera from systemic lupus erythematosus patients. - Hirano, T (J Clin Invest, 1980)
A high incidence of autoantibody against the neutral glycolipid "asialo GM1" was observed in sera from patients with systemic lupus erythematosus (SLE) with neurological disorders, using an immunoflocculation test. The sera from 14 out of 17 cases of SLE with neurological disorders showed antibody activity against asialo GM1 but not against the following glycolipids: asialo GM2 GM1, and galactocerebroside. In another 87 cases of SLE without any history of seizures, as well as 61 cases of other autoimmune diseases (rheumatoid arthritis, progressive systemic sclerosis, mixed connective tissue disease, etc.) and 20 cases of various neurological diseases (epilepsy, multiple sclerosis, etc.), no antibody could be detected. In general, the antibody titer was high several months, even years, before and/or after the seizure, though the titer was low at the time that patients showed definite neurological symptoms. Immunochemical characterization with Sephadex G-200 chromatogrphy and protein A-Sepharose CL-4B affinity column indicated that the antiasialo GM1 was probably an autoantibody belonging to the immunoglobulin G class. The above results suggest that this newly found autoantibody plays a role in the pathogenesis of neurological disorders accompanying SLE. IMAGES: